Synthesis and Enzymatic Deprotection of Fully Protected 2 '-5 ' Oligoadenylates (2-5A): Towards a Prodrug Strategy for Short 2-5A - Kiuru E; Ora M; Beigelman L; Blatt L; Lonnberg H (WILEY-V C H VERLAG GMBH, 2022)
Fully protected pA2'p5'A2'p5'A trimers 1a and 1b have been prepared as prodrug candidates for a short 2'-5' oligoadenylate, 2-5A, and its 3'-O-Me analog, respectively. The kinetics of hog liver carboxyesterase (HLE)-triggered deprotection in HEPES buffer (pH 7.5) at 37 degrees has been studied. The deprotection of 1a turned out to be very slow, and 2-5A never appeared in a fully deprotected form. By contrast, a considerable proportion of 1b was converted to the desired 2-5A trimer, although partial removal of the 3'-O-[(acetyloxy)methyl] group prior to exposure of the adjacent phosphodiester linkage resulted in 2',5'?3',5' phosphate migration and release of adenosine as side reactions.